(untitled) (Vietnam Journal of Community Medicine, 2022)
A descriptive cross sectional study was conducted in pregnant women at Nghe An Obstetrics and Pediatrics Hospital in 2019 to determine the prevalence and risk factors for Group B Streptococcus (GBS) infection in women at the 35th to 37th week of pregnancy. Objective and method: A total of 750 women at the 35th to 37th week of pregancy were enrolled into the study. Clinical examinations, interview, GBS culture and CAM test were employed. Results: Showed that the prevalence of GBS was 9.2%. Related factors included use of unsanitary water sources (OR = 1.86, 95%CI (1.36 - 4.59), p < 0.05); improper vaginal hygiene (OR = 1.74, 95%CI (1.16 - 4.36), p < 0.05); history of GBS infection (OR = 1.98, 95%CI (1.64 - 4.15), p < 0.05); and no habits of daily vulvar wash (OR = 3.0, 95%CI (1.42 - 7.59), p < 0.05).